Impact of SLCO1B1*5 on Flucloxacillin and Co-Amoxiclav–Related Liver Injury - Alshabeeb, Mohammad; Alomar, Fadhel A.; Khan, Amjad (Frontiers in Pharmacology, 2022)
Abstract Background Idiosyncratic drug-induced liver injury (DILI) is a serious uncommon disease that may develop as a result of intake of certain drugs such as the antimicrobials flucloxacillin and co-amoxiclav. The reported cases showed significant associations between DILI and various human leukocyte (HLA) markers. The solute carrier organic anion transporter 1B1 (SLCO1B1), a non-HLA candidate gene, was previously reported as a risk factor for liver injury induced by rifampin and methimazole. This study presumed that SLCO1B1 may play a general role in the DILI susceptibility and therefore investigated the association of rs4149056 (SLCO1B1*5, T521C) polymorphism with flucloxacillin- and co-amoxiclav-induced liver injury. Results A small number of cases failed to genotype in each cohort. Thus, only 149 flucloxacillin and 162 co-amoxiclav DILI cases were analyzed. Genotyping of both DILI cohorts did not show an evidence of association with the variant rs4149056 (T521C) (OR=0.71, 95% CI= 0.46–1.12; P=0.17 for flucloxacillin cases and OR=0.87, 95% CI= 0.56–1.33; P=0.58 for co-amoxiclav); although, slightly lower frequency (22.8%) of positive flucloxacillin cases was noticed compared to POPRES controls (29.4%). ConclusionCarriage of the examined allele SLCO1B1*5 is not considered a risk factor for flucloxacillin DILI or co-amoxiclav DILI as presumed. Testing a different allele (SLCO1B1*15) and another family member gene (SLCO1B3) may still be needed to provide a clearer role of SLCO1B drug transporters in DILI development related to the chosen antimicrobials.